2020
DOI: 10.1097/inf.0000000000002510
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Seroprevalence and Birth Prevalence of Congenital CMV Infection in Bosnia and Herzegovina

Abstract: Background: Congenital cytomegalovirus infection (cCMV) is a leading cause of sensorineural hearing loss (SNHL) and neurodevelopmental disabilities in developed countries. Although high cCMV rates have been reported in populations with high seroprevalence, the cCMV prevalence in low/middle-income countries in Europe has not been defined. Objective: To determine cytomegalovirus (CMV) seroprevalence and the cCMV prevalence in Bosnia and Herzegovina. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Furthermore, above mentioned recent study showed overall seroprevalence of 81.4% among all patients and gender difference in patients older than 20 years were not demonstrated. 22 Also, results from our study did not show difference in CMV seroprevalence related to the gender among children and the overall CMV seroprevalence among paediatric population was 56.5% showing for the first time valuable results paediatric population in Bosnia and Herzegovina. Furthermore, we can conclude that CMV seroprevalence among paediatric population in Bosnia and Herzegovina is higher than in most western European countries, but lower than seroprevalence in Asian and African countries.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Furthermore, above mentioned recent study showed overall seroprevalence of 81.4% among all patients and gender difference in patients older than 20 years were not demonstrated. 22 Also, results from our study did not show difference in CMV seroprevalence related to the gender among children and the overall CMV seroprevalence among paediatric population was 56.5% showing for the first time valuable results paediatric population in Bosnia and Herzegovina. Furthermore, we can conclude that CMV seroprevalence among paediatric population in Bosnia and Herzegovina is higher than in most western European countries, but lower than seroprevalence in Asian and African countries.…”
Section: Discussionmentioning
confidence: 43%
“…20 Recently, the study performed on pregnant women in Tuzla and Mostar in Bosnia and Herzegovina found high CMV seroprevalence of 93% and 92%, respectively. 21,22 In accordance to this, we could presume that CMV seroprevalence among paediatric population in Bosnia and Herzegovina would be same as in low SES and developing countries from Asia or Africa. 5,6 Additionally, Jansen et al found that by the age of three almost all children in countries with low SES were CMV seropositive whereas CMV seroprevalence varies between 40 and 60% among developed European countries.…”
Section: Discussionmentioning
confidence: 74%
“…A total of 77 articles were included in this meta-analysis. The final studies were from 36 countries (eFigure 3 in the Supplement ) on 5 continents and are categorized by World Health Organization regions as follows: Africa, 6 countries (6 studies) 30 , 31 , 32 , 33 , 34 , 35 ; Americas–Latin, 5 countries (9 studies) 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ; Americas–US and Canada, 2 countries (18 studies) 17 , 18 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ; Eastern Mediterranean, 1 country (3 studies) 61 , 62 , 63 ; Europe, 16 countries (24 studies) 8 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ,…”
Section: Resultsmentioning
confidence: 99%
“…These articles reported data for general populations, healthy or immunocompetent populations (ie, without specific diseases and otherwise healthy), and adults. Among adults, seroprevalence ranged most broadly in European countries (44.4-95.7%) [ 32 , 35 37 , 40 , 41 , 48 51 ], with the narrowest range observed for Japanese studies (67.2-70.9%; Fig. 3 ) [ 52 , 53 ].…”
Section: Seroprevalence By Sex and Age Groupmentioning
confidence: 99%